ANALYSIS OF THE RELATIONSHIP BETWEEN SKILLS AND LEADERSHIP STYLE TO DETERMINE THE EFFECT ON MOTIVATION AND LECTURER PERFORMANCE. - Suparjo Suparjo; Lydia Ari Widyarini (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
ABSTRACT This research was conducted to determine and analyze the effect of leadership skills and styles to determine the effect on the motivation and performance of lecturers. This study was chosen because of the phenomena and problems associated with job satisfaction. This, of course, relates to many factors, but the author has a provisional assumption that skills and leadership style factors will determine the effect on lecturer motivation and performance, both of which will affect and increase lecturer job satisfaction and performance. The method used in collecting data in this research is a questionnaire. The number of questionnaires given to respondents was 100 questionnaires. The data analysis technique uses descriptive analysis and questionnaire feasibility tests that have been tested first with validity tests, reliability tests, multicollinearity test, coefficient of determination test and Path analysis (Path Analysis) with smart-pls software. The research gives the following results: The model directly shows that leadership skills and styles have a significant positive effect on increasing lecturers' motivation and performance. In addition, motivation also has a significant positive effect on improving the performance of lecturers, so that the increasing motivation in life will improve the performance of lecturers better. The model indirectly uses motivation as a mediator variable, showing that skills and leadership style have no effect on increasing lecturer performance through motivational mediators The research gives the following results: The model directly shows that leadership skills and styles have a significant positive effect on increasing lecturers' motivation and performance. In addition, motivation also has a significant positive effect on improving the performance of lecturers, so that the increasing motivation in life will improve the performance of lecturers better. The model indirectly uses motivation as a mediator variable, showing that skills and leadership style have no effect on increasing lecturer performance through motivational mediators The study gave the following results: The model directly shows that leadership skills and styles have a significant positive effect on increasing lecturers' motivation and performance. In addition, motivation also has a significant positive effect on improving the performance of lecturers, so that the increasing motivation in life will improve the performance of lecturers better. The model indirectly uses motivation as a mediator variable, showing that leadership skills and styles have no effect on increasing lecturer performance through motivational mediators In addition, motivation also has a significant positive effect on improving the performance of lecturers, so that the increasing motivation in life will improve the performance of lecturers better. The model indirectly uses motivation as a mediator variable, showing that leadership skills and styles have no effect on increasing lecturer performance through motivational mediators In addition, motivation also has a significant positive effect on improving the performance of lecturers, so that the increasing motivation in life will improve the performance of lecturers better. The model indirectly uses motivation as a mediator variable, showing that leadership skills and styles have no effect on increasing lecturer performance through motivational mediators Keywords: skills, leadership style, job satisfaction and performance